ANALYSIS OF NEUTROPHIL-TO-LYMPHOCYTE RATIO, PLATELET-TO-LYMPHOCYTE RATIO, AND VITAMIN D LEVELS IN COVID-19 PATIENTS BASED ON DISEASE SEVERITY - TOLLA, NELLY; BAHRUN, ULENG; FAIDAH, NUR; ANGGERAINI, SALSA; HANUM P, PUDYA; ARAS, DARA UGI; LESTARI, AYU (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2025)
Background:  Patients with COVID-19 experience a range of clinical symptoms, from asymptomatic to multi-organ failure. It is believed that factors including age, gender, systemic disease, and the inflammatory response that takes place have a significant impact in rising morbidity and mortality.3,4 Dysregulation of proinflammatory cytokines might result from the inflammatory response brought on by innate immunity.5 The prognosis of COVID-19 patients is characterized by an elevation in the neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR), which are regarded to be inflammatory marker parameters.3 Because vitamin D is known as an immunomodulator that is essential for addressing the cytokine storm mechanism as disease development in COVID-19 patients, vitamin D deficiency has lately been believed to play a significant role in the success of therapy.6Methods: A cross-sectional descriptive analytic research approach was applied in this study, which included 88 COVID-19 patients from the Hasanuddin Teaching Hospital divided into two groups.Results: The results showed a significant difference between the NLR (2.82 + 1.86 ; 8.09 + 5.40) and PLR (11.35 + 6.98 ; 34.35 + 16.52) in both groups with higher NLR and PLR levels in patients with severe grades. Although vitamin D levels in both groups were within normal limits, vitamin D levels were lower in patients with severe COVID-19 compared to mild-moderate levels with a mean value (19.62 + 7.89 ; 16.62 + 6.28).Conclusion: Vitamin D insufficiency can be considered when evaluating the therapeutic response and NLR and PLR levels can be employed as markers in measuring the inflammatory response.